In Case of Emergency Card - support of the emergency services and victims on accident site as a part of the campaigns to improve road safety - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Lasota, Dorota; Fiedor, Piotr (Journal of Education, Health and Sport, 2017)
Emergency medical services, police, firefighters and all others who provide first aid on-site emergency many times have hardness when they have to inform family or people related with victims. Some years ago italian medical rescuers suggest to mark some number in mobile phone in a special way to make contact with family easier. In the opinions of the Italian rescuers the best way to mark this number is to name it I.C.E. (In Case of Emergency). This kind of mark would make job of medical rescuers easier. More than one number in mobile phone should be called ICE1, ICE2, ICE3, etc. ICE begin in 2005 along the world. Its common in England, Italy, German. In Poland is popular from this year. I.C.E. is promoted by Polish Red Cross.